Forests, Trees and Human Health 2010
DOI: 10.1007/978-90-481-9806-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Forest Products with Health-Promoting and Medicinal Properties

Abstract: Forests are a rich renewable source of health-promoting and medicinal products. Not only the trees but also berries, nuts and mushrooms in forests contain a multitude of natural bioactive compounds which can be used in health-promoting products and medicines. In addition to the main structural components that trees contain, namely cellulose, hemicelluloses and lignin, thousands of bioactive compounds have been identified. Forest products have always had a key role in traditional medicine which continues to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 139 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Studies showed some medicinal effects such as dropping hypertension and pains in the higher part of the abdomen, gastric pains, indigestion and gastric ulcers (Yousefi, 2016). Also mastic gum and essential oils extracted from pistachios are considered natural antimicrobials which have wide usages in Mediterranean countries and the middle east since ancient eras (Gallis et al, 2011). Concerning recently mastic gum usages, they have been expanded more and more where they were used in making sorting fibers used in surgery for being absorbed by the human body and also used as a sterilization for mouth and stretching for gums (Al-Mofraji et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed some medicinal effects such as dropping hypertension and pains in the higher part of the abdomen, gastric pains, indigestion and gastric ulcers (Yousefi, 2016). Also mastic gum and essential oils extracted from pistachios are considered natural antimicrobials which have wide usages in Mediterranean countries and the middle east since ancient eras (Gallis et al, 2011). Concerning recently mastic gum usages, they have been expanded more and more where they were used in making sorting fibers used in surgery for being absorbed by the human body and also used as a sterilization for mouth and stretching for gums (Al-Mofraji et al, 2013).…”
Section: Introductionmentioning
confidence: 99%